Niger : Sixth Review Under the Extended Credit Facility and Request for Waiver for Nonobservance of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2020)
With one of the world's lowest levels of human development, Niger has enormous needs but only limited own resources to meet them. Insecurity in the Sahel, climate change, and low prices for its uranium exports are further challenges. Niger's economy performed reasonably well before the outbreak of the COVID-19 pandemic. GDP growth exceeded 6 percent and large foreign projects were attracted, notably a pipeline for the export of crude oil. A new government will take office in April 2021.